WEAK BEAUTIFUL PEOPLE FAMILY DYSFUNCTION AND THE AMERICAN DREAM IN TENNESSEE WILLIAMS'S CAT ON A HOT TIN ROOF - Cascella, Laura M. (My University, 2010)
This project evaluates how dysfunctional filial relationships in Tennessee Williams's Cat on a Hot Tin Roof are a metaphor for the failed American Dream of happiness, success, and comfort. First published in 1955, Cat portrays the tragic and hostile relationships of one Southern family during the 1950s a fragile time in American history. This analysis of the family dynamics in Cat will help explain the tensions, pressures, beliefs, and values that the family unit generated, and how those aspects related to and reflected American society at large during the 1950s. This research will build on existing scholarship dedicated to American domestic drama and will help explore the ways in which family relationships shape individual and national identity, and how, like theatre itself, the American family in drama serves as a microcosm of the American experience. For this research, a number of sources were used, including the text of Cat on a Hot Tin Roof scholarship focusing on the portrayal of the family in American drama; literary criticism and interpretation of Williams and the aforementioned play; research that examines and analyzes themes, patterns, symbolism, and methods in American drama; cultural studies of the American family, gender identity, and sexuality in mid-twentieth century America; and historical analyses of America during the 1950s and the social and political climate during the postwar and early Cold War years.